Diffusion tensor tractography to visualize axonal outgrowth and regeneration in a 4-cm reverse autograft sciatic nerve rabbit injury model. (4th March 2019) - Farinas, Angel F.; Pollins, Alonda C.; Stephanides, Michael; O'Neill, Dillon; Al-Kassis, Salam; Esteve, Isaac V. Manzanera; Colazo, Juan M.; Keller, Patrick R.; Rankin, Timothy; Wormer, Blair A.; Kaoutzanis, Christodoulos; Dortch, Richard D.; et al.
ABSTRACT: Background : Diffusion tensor tractography (DTT) has recently been shown to accurately detect nerve injury and regeneration. This study assesses whether 7-tesla (7T) DTT imaging is a viable modality to observe axonal outgrowth in a 4 cm rabbit sciatic nerve injury model fixed by a reverse autograft (RA) surgical technique. Methods : Transection injury of unilateral sciatic nerve (4 cm long) was performed in 25 rabbits and repaired using a RA surgical technique. Analysis of the nerve autograft was performed at 3, 6, and 11 weeks postoperatively and compared to normal contralateral sciatic nerve, used as control group. High-resolution DTT from ex vivo sciatic nerves were obtained using 3D diffusion-weighted spin-echo acquisitions at 7-T. Total axons and motor and sensory axons were counted at defined lengths along the graft. Results : At 11 weeks, histologically, the total axon count of the RA group was equivalent to the contralateral uninjured nerve control group. Similarly, by qualitative DTT visualization, the 11-week RA group showed increased fiber tracts compared to the 3 and 6 weeks counterparts. Upon immunohistochemical evaluation, 11-week motor axon counts did not significantly differ between RA and control; but significantly decreased sensory axon counts remained. Nerves explanted at 3 weeks and 6 weeks showed decreased motor and sensory axon counts. Discussion : 7-T DTT is an effective imaging modality that may be used qualitatively to visualize axonal outgrowth and regeneration. This has implications for the development of technology that non-invasively monitors peripheral nerve regeneration in a variety of clinical settings.